Majjallat Al-Ahkam Al-‘Adliyyah: Position and Influence on the Development of Fiqh - Salman Abdul Muthalib (Sharia and Law Faculty, 2022)
The establishment of Majjallat al-Ahkam al-'Adliyyah as the first qanun in Turkey was a new breakthrough in the development of Islamic law during the Ottoman period. The authority of Islamic law, which was previously in the hands of the ulama, had shifted to the rulers. The diversity of laws that existed had merged into uniformity in their implementation. This research will examine the style and scope of the content of Majjallat al-Ahkam al-'Adliyyah, its position in the development of Fiqh, and the influence of the Majallah in Islamic countries. This research is a literature study, with Majjallat al-Ahkam al-'Adliyyah as the main data source. The results show that the Majallah is a civil law whose material is taken from the Hanafi school, containing discussions only about muamalah law, and its writing is accompanied by numbering, similar to modern legislation. The emergence of the Majallah is considered a new period in the development of fiqh, where there has been a shift from the period of taqlid towards efforts of ijtihad among scholars. The Majallah gave birth to the pattern of collective ijtihad and became the law of the state. The Majallah has encouraged several Islamic countries to design laws by referring to the pattern of the Majallah. Ditetapkannya Majjallat al-Ahkam al-‘Adliyyah sebagai qanun pertama di Turki merupakan terobosan baru dalam perkembangan hukum Islam pada masa Turki Utsmani. Di mana wewenang hukum Islam yang sebelumnya berada pada tangan ulama telah berpindah ke tangan penguasa. Keberagaman hukum yang ada telah menyatu menjadi keseragaman dalam pelaksanaannya. Penelitian ini akan mengkaji corak dan cakupan isi Majjallat al-Ahkam al-‘Adliyyah, posisinya dalam perkembangan Fiqh, dan pengaruh Majallah di negara-negara Islam. Penelitian ini bersifat studi kepustakaan, dengan menjadikan kitab Majjallat al-Ahkam al-‘Adliyyah sebagai sumber data utama. Hasil penelitian menunjukkan bahwa Majallah merupakan hukum perdata yang materinya diambil dari mazhab Hanafi, berisikan bahasan tentang hukum muamalah saja, penulisannya telah disertai dengan penomoran seperti dalam perundangan-undangan modern. Lahirnya Majallah dianggap menjadi periode baru dalam perkembangan fiqh, dimana telah terjadi pergeseran dari periode taklid menuju upaya-upaya ijtihad di kalangan ulama. Majallah melahirkan bentuk pola ijtihad jama'i dan menjadi undang-undang negara. Majallah telah mendorong beberapa negara Islam terinspirasi untuk merancang undang-undang dengan merujuk pada pola Majallah.